2020
DOI: 10.1039/d0cp03265d
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal-like aggregation of a functional amyloid protein

Abstract: Functional amyloid proteins are self-secreted by microbial cells that aggregate into extracellular networks and provide microbial colonies with mechanical stability and resistance to antibiotic treatment. In order to understand the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Unlike curli, the amyloid fibres that are produced by Escherichia coli and other enteric bacteria (reviewed elsewhere 23 ), monomeric TasA in B. subtilis is globular in solution and adopts a jelly-roll-like fold with a flexible helix-rich region 29 . At low pH, TasA forms dense gel-like networks that are comparable to colloidal aggregation 30 . Transmission electron microscopy (TEM) imaging of TasA fibres consistently reveals repeating units along the protofilament (smallest diameter fibres) axis that are estimated to be ~5 nm in length 22,28 , similar to the size of the TasA monomer.…”
Section: [H1] Introductionmentioning
confidence: 99%
“…Unlike curli, the amyloid fibres that are produced by Escherichia coli and other enteric bacteria (reviewed elsewhere 23 ), monomeric TasA in B. subtilis is globular in solution and adopts a jelly-roll-like fold with a flexible helix-rich region 29 . At low pH, TasA forms dense gel-like networks that are comparable to colloidal aggregation 30 . Transmission electron microscopy (TEM) imaging of TasA fibres consistently reveals repeating units along the protofilament (smallest diameter fibres) axis that are estimated to be ~5 nm in length 22,28 , similar to the size of the TasA monomer.…”
Section: [H1] Introductionmentioning
confidence: 99%
“…Facing the presence of cross beta sheet fingerprint in intact biofilms, its increase in the presence of TasA (in 24-and 72-hour WT samples) and in light of the literature debate on the amyloid nature of TasA (28,31,51,52), we were intrigued to learn more about the structure and composition of fibers formed in vitro from isolated TasA preparations. Recently, we have shown that TasA is polymorphic, as it forms fibers with different morphologies: aggregates in acidic solutions (termed 'aggregates' henceforth), thin and long fibers at high salt concentrations (termed 'fibrils' henceforth) and fiber bundles at high protein and salt concentration (henceforth termed' bundles') (30,53,54). A-C) XRF of TasA fibers, (A) formed in acidic conditions ('TasA aggregates), (B) high salt concentration ('TasA fibrils'), and (C) high protein and salt concentration ('TasA bundles').…”
Section: Tasa Harbors a Minimal Cross-beta Domain And Binds Metal Ionsmentioning
confidence: 99%
“…Recently, we have shown that TasA is polymorphic, as it forms fibers with different morphologies: aggregates in acidic solutions (termed 'aggregates' henceforth), fiber bundles at high protein and salt concentration (termed 'bundles' henceforth) and thin and long fibers at high salt concentrations (termed 'fibrils' henceforth). 30,56,57 .…”
Section: Tasa Harbors a Minimal Cross- Domain And Binds Metal Ionsmentioning
confidence: 99%
See 2 more Smart Citations